2010
DOI: 10.1111/j.1600-6143.2009.02984.x
|View full text |Cite
|
Sign up to set email alerts
|

Harm and Benefits of Primary Liver Resection and Salvage Transplantation for Hepatocellular Carcinoma

Abstract: Primary transplantation offers longer life-expectancy in comparison to hepatic resection (HR) for hepatocellular carcinoma (HCC) followed by salvage transplantation; however, livers not used for primary transplantation can be reallocated to the remaining waiting-list patients, thus, the harm caused to resected patients could be balanced, or outweighed, by the benefit obtained from reallocation of livers originating from HCC patients first being resected. A Markov model was developed to investigate this issue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 42 publications
5
47
1
Order By: Relevance
“…The most important result of this intention-totreat study was that approximately half of our patients with HCC recurrence following LR did not undergo transplantation, including one-third because of recurrence beyond the MC. This result is a matter of debate concerning the respective roles of LR and LT in the treatment of HCC [7,73,76]. Analysis of the subgroup of patients who could not undergo transplantation at the time of recurrence showed that three factors were associated with failure.…”
Section: Treatment On the Waiting Listmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important result of this intention-totreat study was that approximately half of our patients with HCC recurrence following LR did not undergo transplantation, including one-third because of recurrence beyond the MC. This result is a matter of debate concerning the respective roles of LR and LT in the treatment of HCC [7,73,76]. Analysis of the subgroup of patients who could not undergo transplantation at the time of recurrence showed that three factors were associated with failure.…”
Section: Treatment On the Waiting Listmentioning
confidence: 99%
“…Initial LR of HCC as primary therapy in patients who otherwise could have been transplanted offers good quality of life and is less demanding than LT. Patients do not need long-term immunosuppression; in addition, grafts are saved for the community and can be transplanted to other patients with no alternative to LT [7,9,73]. For LR as primary therapy for tumor recurrence or deterioration in liver function, "salvage transplantation" was first proposed by Majno et al [75] This attractive concept seems to be applicable in a significant proportion of patients with long-term survival similar to that of patients who undergo primary LT [9,73,76].…”
Section: Treatment On the Waiting Listmentioning
confidence: 99%
“…9 Expansion of criteria for LT in HCC patients is still under investigation and discussion. 10,11 The limited availability of donors for LT, has led to considerable interest for expansion of the donor pool and living donor-related transplantation, 12 and combined treatments involving LR and LT. 9,13 This review presents and discusses recent advances in the surgical treatment of HCC. Advances in the assessment of liver function are also described, along with discussion of patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Since MELD priority points were awarded by UNOS from 2002 even for lesions ≤2 cm, the SEER data probably included significant numbers of such cases before revision of points by UNOS. Mathematical models have computed that unless there is more than 30% progression related wait list dropout among patients and more than 10% waitlisted patients for LT have HCC as indication, preferential allocation to HCC patients increases wait list mortality among those not having HCC [32].…”
mentioning
confidence: 99%